2021
DOI: 10.1007/s10811-021-02577-y
|View full text |Cite
|
Sign up to set email alerts
|

Thorsmoerkia curvula gen. et spec. nov. (Trebouxiophyceae, Chlorophyta), a semi-terrestrial microalga from Iceland exhibits high levels of unsaturated fatty acids

Abstract: A terrestrial green alga was isolated at Iceland, and the strain (SAG 2627) was described for its morphology and phylogenetic position and tested for biotechnological capabilities. Cells had a distinctly curved, crescent shape with conical poles and a single parietal chloroplast. Phylogenetic analyses of 18S rDNA and rbcL markers placed the strain into the Trebouxiophyceae (Chlorophyta). The alga turned out to belong to an independent lineage without an obvious sister group within the Trebouxiophyceae. Based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Another green microalga, Chlamydomonas reinhardtii , showed a FAs profile similar to those of E. pseudoalveolaris , being palmitic acids, among SFAs, and ALA, among PUFAs, the most represented FAs [ 43 ]. A study by Nicoletti et al [ 44 ] found that the green microalga Thorsmoerkia curvula also contained significant amounts of ALA, thus confirming the potential of green microalgae as a viable source of ALA with various applications in food, nutraceuticals and animal feed. Although to a lesser extent then PUFAs, monounsaturated fatty acids (MUFAs) were also present in the FAs profile of Ettlia , with palmitoleic (3.35 ± 0.03%) and oleic acid (3.28 ± 0.02%) as the most represented.…”
Section: Resultsmentioning
confidence: 94%
“…Another green microalga, Chlamydomonas reinhardtii , showed a FAs profile similar to those of E. pseudoalveolaris , being palmitic acids, among SFAs, and ALA, among PUFAs, the most represented FAs [ 43 ]. A study by Nicoletti et al [ 44 ] found that the green microalga Thorsmoerkia curvula also contained significant amounts of ALA, thus confirming the potential of green microalgae as a viable source of ALA with various applications in food, nutraceuticals and animal feed. Although to a lesser extent then PUFAs, monounsaturated fatty acids (MUFAs) were also present in the FAs profile of Ettlia , with palmitoleic (3.35 ± 0.03%) and oleic acid (3.28 ± 0.02%) as the most represented.…”
Section: Resultsmentioning
confidence: 94%
“…This initial physiological characterization indicates great potential for future industrial use of C. terrestris WP154.1 for both, scalable adonixanthin and polyunsaturated FA production. Due to its climate, Iceland seems to be a promising origin of microbial strains useful for biotechnology, as recently shown for another green microalga [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sequences of ACOI 2681 and 3192 were identical for all three molecular markers sequenced and thus we treat these two strains as conspecific. The VMJ + ACOI 2681/3192 cluster was then sister to the Icelandic Thorsmoerkia curvula described by Nicoletti et al (2021) (Fig. 16).…”
Section: Phylogenetic Analysesmentioning
confidence: 91%
“…In some cases, such organisms form deeply branching isolated lineages. A notable example is the recently described semi-aerophytic crescent-shaped Thorsmoerkia curvula, which was not assigned to any of the existing orders or clades and allegedly lacked sequenced close relatives (Nicoletti et al, 2021). Another example of an enigmatic and phylogenetically unresolved lineage is represented by a Navicula-shaped coccoid alga (strain SAG 2477) isolated from soil in Germany, provisionally considered a candidate new species in a new genus in a PhD thesis (Hodač, 2015).…”
Section: Introductionmentioning
confidence: 99%